TEN OF MARX'S IDEAS THAT SURVIVED THE 20TH CENTURY - Šijaković, Ivan (Politeia, 2019)
This paper analyses some of Marx's ideas and attitudes that have been the subject of debate, support, dispute and controversy during the 20th century. All these ideas, in the second decade of the 21st century, can be the basis for research, analysis and criticism of the same phenomena Marx spoke about 150 or 160 years ago. In this paper, we point out ten key ideas of Karl Marx that were theoretically important for the analysis of events and social changes during the XX and early XXI centuries.
Keywords: Marx; emancipation; exploitation; poverty; machine; fictitious capital